APPLICATION OF INNOVATIVE TECHNOLOGIES IN MUSEUMS - Жандарбекова, Таншолпан (SWorldJournal, 2021)
The paper considers innovative technologies used in museum buildings. In the XXI century, information technologies are often used in various industries. A huge number of companies use them in their fields of activity, sometimes even at the state level. Th